CONSERVATION OF MEDICINAL PLANTS OF KASHMIR J&K (UT) BY EX-SUITA CONSERVATION TECHNIQUES - Mr Sartaj Ahmad, Bilal Ahmaddar, Mehraj ud din Khanday, (Chelonian Research Foundation, 2023)
The present study reports the conservation strategies of medicinal plants of Kashmir (UT) in the year 2022-2023. World Health organization has listed about 21000 plants species used worldwide for Ayurvedic medicinal purpose. In our country about 2500 plant species are being used in native system of medicines. As per Red bookdata, 427 Indian medicinal plants entries onendangered speices,28 are considered extinct. 125 engendered,82 rare and 35 insufficient known. As medicinal plants are used as first aid treatment by the tribal and local people of Kashmir(UT). Medicinal plants have played a very significant role in the health and live hood security of the people of Jammu and Kashmir (UT) therefore their conservation is also necessary. Many ways of action can be taken for the conservative and sustainable use of medicinal plants. Some of them are undertaken directly at the placewhere the plants are found. While other are less direct relating to commercial system. Ex suita conservation, one of which is conservation of medicinal plants by floating garden and Hydroponic technique has not only conservation value but also recreation and aesthetic value Keywords: Conservation of medicinal plant, floating gardens, hydroponic technique